2020
DOI: 10.33448/rsd-v9i9.7526
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento cirúrgico de osteoma periosteal em mandíbula – relato de caso

Abstract: Introdução: Os osteomas são proliferações de tecido ósseo, neoplasia benigna clinicamente consiste em massa bem delimitada que pode ser séssil ou pediculada, assintomática e que dependendo da sua localização e tamanho, pode acarretar  danos a estruturas adjacentes, alterações funcionais e estéticos dependendo da sua localização. Objetivo: Discutir um relato de caso de osteoma periosteal compacto em região mandibular. Relato de Caso: Paciente N.B, do sexo feminino, 33 anos, foi atendida no Hospital da face (Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Conditions associated with the persistence of the embryonic periosteum have also been related to the development of the lesion, especially in cases in which researchers were unable to establish the relationship between the beginning of its Research, Society and Development, v. 10, n. 6, e4810615486, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.15486 development and the occurrence of trauma or previous inflammatory processes (Bullot, et al, 2010;Aires, et al, 2020). In the present case, the patient was not exposed to any inflammatory or traumatic episode in the mandible region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conditions associated with the persistence of the embryonic periosteum have also been related to the development of the lesion, especially in cases in which researchers were unable to establish the relationship between the beginning of its Research, Society and Development, v. 10, n. 6, e4810615486, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.15486 development and the occurrence of trauma or previous inflammatory processes (Bullot, et al, 2010;Aires, et al, 2020). In the present case, the patient was not exposed to any inflammatory or traumatic episode in the mandible region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have shown that computed tomography is the ideal imaging test to determine the actual location and extent of the lesion, as it is a versatile test that produces detailed images of bone tumors, with good sensitivity and great specificity for abnormalities. Cone-beam computed tomographies also reproduce detailed images with high specificity but are obtained with a lower dose of radiation; such a characteristic must be taken into account when choosing the ideal exam (Shintaku et al, 2010;Bullot et al, 2010;Aires et al, 2020). In the case in question, conventional computed tomography was chosen, since in addition to the excellent image reproduction properties, it is an exam available in the Unified Health System, thus not generating additional costs for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations